The effect of Moringa oleifera crude extract on liver cell line, HepG2 - Boluwatife O. Sowunmi; Martin Gonzo (BMC, 2023)
Abstract Background The liver plays a crucial role in the body's metabolic and detoxification processes. Given its importance, compromised liver function can negatively impact the body's metabolic and physiological function. Liver diseases can result from several factors, including exposure to toxins, alcohol consumption, and viral infections. Therefore, finding natural remedies for liver protection and treatment is important. Moringa oleifera is a tree known for its various medicinal properties, including hepatoprotective effects. This study aimed to investigate the potential of M. oleifera seed extract in protecting liver cells. Methods In this study, dried-seed powder of M. oleifera was extracted using extraction solvents, methanol, and ethanol. HepG2 cells were cultured and treated with different concentrations of the extracts. The antioxidative activity, cell viability, and antiproliferation were assessed using the total antioxidant capacity assay (TAC) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Additionally, liver enzyme activity was determined through alkaline phosphatase and aspartate aminotransferase activity assays. Results The extracts had varying effects on liver cells depending on the concentration and time of exposure. Lower concentrations (50 mg/l and 100 mg/l) have mild stimulatory effects/minimal impact on metabolic activity, while higher concentrations (200 mg/l and 400 mg/l) tend to decrease metabolic activity, especially at later time points. Moreover, the extracts effectively reduced the levels of the liver enzyme AST, indicating their ability to mitigate liver injury. Conclusion The study concludes that the crude extracts of M. oleifera seeds exhibit potential as a natural remedy for liver diseases. The effects of M. oleifera extract suggest that it has potential as a preventive and therapeutic agent for liver damage. This study highlights the importance of exploring natural remedies for liver protection and treatment.